Bile acids trigger cholemic nephropathy in common bile‐duct–ligated mice. Issue 6 (15th October 2013) - Fickert, Peter; Krones, Elisabeth; Pollheimer, Marion J.; Thueringer, Andrea; Moustafa, Tarek; Silbert, Dagmar; Halilbasic, Emina; Yang, Min; Jaeschke, Hartmut; Stokman, Geurt; Wells, Rebecca G.; Eller, Kathrin; et al.
<x xml:space="preserve">Abstract</x> Tubular epithelial injury represents an underestimated but important cause of renal dysfunction in patients with cholestasis and advanced liver disease, but the underlying mechanisms are unclear. To address the hypothesis that accumulation and excessive alternative urinary elimination of potentially toxic bile acids (BAs) may contribute to kidney injury in cholestasis, we established a mouse model for detailed in vivo time course as well as treatment studies. Three‐day common bile duct ligation (CBDL) induced renal tubular epithelial injury predominantly at the level of aquaporin 2–positive collecting ducts with tubular epithelial and basement membrane defects. This was followed by progressive interstitial nephritis and tubulointerstitial renal fibrosis in 3‐, 6‐, and 8‐week CBDL mice. Farnesoid X receptor knockout mice (with a hydrophilic BA pool) were completely protected from CBDL‐induced renal fibrosis. Prefeeding of hydrophilic norursodeoxycholic acid inhibited renal tubular epithelial injury in CBDL mice. In addition, we provide evidence for renal tubular injury in cholestatic patients with cholemic nephropathy. Conclusion: We characterized a novel in vivo model for cholemic nephropathy, which offers new perspectives to study the complex pathophysiology of this condition. Our findings suggest that urinary‐excreted toxic BAs represent a pivotal trigger for renal tubular epithelial injury leading to cholemic nephropathy in CBDL mice. (Hepatology 2013; 58:2056–2069)